2012
DOI: 10.1073/pnas.1121256109
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early intervention and the moderating effects of brain activity on institutionalized children's social skills at age 8

Abstract: The present study examined the social skills of previously institutionalized, 8-y-old Romanian children from the Bucharest Early Intervention Project and the influence of attachment security and brain electrical activity (alpha power) on these skills. Participants included children randomized to an intervention involving foster care [Foster Care Group (FCG)], children randomized to remain in institutions [Care As Usual Group (CAUG)], and neverinstitutionalized children living with their families in the Buchare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
45
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(51 citation statements)
references
References 28 publications
6
45
0
Order By: Relevance
“…As an example of sensitive period, animal studies have demonstrated that very early disruptions in maternal care can permanently alter attachment-related neural functioning and emotional learning (RincĂłn-CortĂ©s & Sullivan, 2014). Furthermore, the studies of institutionalized and then adopted children suggest that the first 2 years of life are especially important for social skills (Almas et al, 2012), and the second year of life is especially important for executive functions (Merz, McCall, Wright, & Luna, 2013). However, research is lacking about the more normative social experiences within the infancy period.…”
Section: Age-specific Development During Infancymentioning
confidence: 99%
“…As an example of sensitive period, animal studies have demonstrated that very early disruptions in maternal care can permanently alter attachment-related neural functioning and emotional learning (RincĂłn-CortĂ©s & Sullivan, 2014). Furthermore, the studies of institutionalized and then adopted children suggest that the first 2 years of life are especially important for social skills (Almas et al, 2012), and the second year of life is especially important for executive functions (Merz, McCall, Wright, & Luna, 2013). However, research is lacking about the more normative social experiences within the infancy period.…”
Section: Age-specific Development During Infancymentioning
confidence: 99%
“…For example, security of attachment at 42 months among children with histories of institutional rearing predicted reductions in internalizing signs in girls at 54 months, sustained levels of stable, typical IQ scores through age 12 years (Almas et al, 2016), social skills at 8 years (Almas et al, 2012), a reduction in callous unemotional traits in boys at 12 years (Humphreys, McGoron et al, 2015), and overall competence at 12 years (Humphreys, Miron, McLaughlin, Sheridan, Nelson, Fox, & Zeanah, under review). …”
mentioning
confidence: 99%
“…In a parallel human experiment, Weikum et al (34) describe how a serotonin reuptake inhibitor antidepressant and prenatal maternal mood co-operate to shift developmental milestones related to language acquisition. Finally, Almas et al (35), in data from their ongoing, random assignment experiment among previously institutionalized Romanian children, report statistical interaction effects of attachment security and EEG activity on the acquisition of social skills. These papers provide substantive and unique insights into how the acquisition of skills and capacities, within specific developmental domains and during critical periods of heightened environmental sensitivity, can be altered by perceptual, pharmacological, and social signaling.…”
mentioning
confidence: 99%